Controlled trial of imipramine in diurnal enuresis. Issue 9 (September 1982) - Meadow, R; Berg, I
Abstract : Twenty-seven children with diurnal enuresis were studied in a double-blind randomised controlled trial of imipramine. Outcome was not related to such features as age, gender, maximum functional bladder capacity, or evidence of psychiatric disturbance. Although the condition in several children improved, no evidence emerged to suggest that imipramine was superior to placebo in the treatment of the condition.